2014
DOI: 10.4103/0973-029x.141370
|View full text |Cite
|
Sign up to set email alerts
|

Oral mucocele: A clinical and histopathological study

Abstract: Background:Oral mucocele is the most common benign minor (accessory) salivary gland lesion, caused due to mechanical trauma to the excretory duct of the gland. Clinically they are characterized by single or multiple, soft, fluctuant nodule, ranging from the normal color of the oral mucosa to deep blue. It affects at any age and is equally present in both sexes with highest incidence in second decade of life. They are classified as extravasation or retention type.Objectives:To analyze the data between 2010 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
88
1
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(104 citation statements)
references
References 9 publications
6
88
1
9
Order By: Relevance
“…Which is comparable with studies of, Mishra et al 19 In present study oral Mucocele was most commonly found in male in 10-20 years of age group and most common site was lower lip. This is comparable to More et al and Oliveira et al 20,21 For Mucocele male to female ratio in present study was M: In present study, pyogenic granuloma was most commonly seen in age group of 21-30 years. This is similar to study of Kadeh et al In present study male to female ratio was M:F 2:1 which is in contrast with study of Kadeh et al In present study most common site for pyogenic granuloma was buccal mucosa but Kadeh et al study found gingiva as the most common site for pyogenic granuloma.…”
Section: Discussionsupporting
confidence: 80%
“…Which is comparable with studies of, Mishra et al 19 In present study oral Mucocele was most commonly found in male in 10-20 years of age group and most common site was lower lip. This is comparable to More et al and Oliveira et al 20,21 For Mucocele male to female ratio in present study was M: In present study, pyogenic granuloma was most commonly seen in age group of 21-30 years. This is similar to study of Kadeh et al In present study male to female ratio was M:F 2:1 which is in contrast with study of Kadeh et al In present study most common site for pyogenic granuloma was buccal mucosa but Kadeh et al study found gingiva as the most common site for pyogenic granuloma.…”
Section: Discussionsupporting
confidence: 80%
“…7,8 Other lesions are the papillary cystadenoma 9 and the sialolipoma 10 ; salivary gland lesions comprise mainly the salivary duct cyst 11 and mucoceles. 12 The labial minor salivary glands are an ideal source for minimal invasive recruitment of potential 656940J HCXXX10.1369/0022155416656940Human labial glandsStoeckelhuber et al…”
Section: Introductionmentioning
confidence: 99%
“…Mucocele is a painless oral lesion more prevalent in young [1][2][3]6,21 and adolescent age group, therefore the present study included pa ents who were below 20 years of age. In the present study number of females exceeded males, however, previous published literatures do not show gender 1,6,21 predilec on.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally asymptoma c, single, painless, 1 smooth, so , spherical translucent and fluctuant nodule. It is most frequently seen in young and adolescent age groups [2][3][4] and rarely among children under one year of age. Although minor salivary glands are found in most parts of the oral cavity except the gingiva, mucocele occur most commonly in the lower lip, probably due to the higher incidence of 5 mechanical trauma in this region.…”
Section: Introductionmentioning
confidence: 99%